Assignment of hybrid laser and microwave inter-satellite links for navigation satellite systems - Nan Wang; Leyuan Sun; Yuankun Fang; Zhengkai Lu; Qiancheng Ding; Chengzhuo Wang; Wende Huang (Scientific Reports)
Abstract A hybrid network comprising both laser and microwave inter-satellite links (ISLs) has been established within navigation satellite constellations. Leveraging the flexible construction of microwave links and the high ranging accuracy and communication efficiency of laser links, a collaborative link scheme was proposed. With Position Dilution of Precision (PDOP) and communication delay serving as performance indices, multi-objective optimization models for hybrid ISLs were established, incorporating complex constraints. Assignment algorithms based on Non-dominated Sorting Genetic Algorithm II (NSGA-II) and the standard Genetic Algorithm (GA) were proposed. The effectiveness of the collaborative link scheme and the assignment algorithms was evaluated through simulations. The results indicated that each satellite could establish 18.4 ISLs per minute on average. The average PDOP of hybrid links for geosynchronous orbit (GEO) / inclined geosynchronous orbit (IGSO) and medium Earth orbit (MEO) satellites were 1.5 and 1.1, respectively. The average communication delay from overseas to anchor satellites via pure laser links was approximately 0.15 s. When some laser links were unavailable, the remaining available laser ISLs could collaborate with microwave ISLs to provide a transmission route with a maximum delay of 3.2 s. It was demonstrated that the collaborative link scheme and assignment algorithms effectively addressed the hybrid link assignment problem, considering both inter-satellite ranging and communication.